MENEMUKAN KEMBALI KAPITAL SOSIAL BANGSA INDONESIA - Mahdi, Haris El; Suryadi, Suryadi (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
As a nation-state, Republic of Indonesia has been having the long history. Come from inequality and plurality of tribes, ethnics, and religions; Indonesia effort to fight against Colonialism. In history, this struggle doesnât success before declared Sumpah Pemuda. All of youth organizations in Indonesia declare a vow that Indonesia is one nation, one language and one motherland. This declares is the first movement toward Indonesian unity. In otherwise, Sumpah Pemuda is basic for the power of social capital of Indonesia. In recent time, to fight against all of nationality problems, we must find the power of social capital again. This article further argues that Indonesia has abstract systems â especially Pancasila â as basic and keeper for social capital of Indonesia. Key words: Sumpah Pemuda, Social Capital, Abstract Systems